The Effect of Sales Promotion and Customer Satisfaction on Interest to Buy Gadgets - Darman (Eastasouth Institute, 2023)
This study aims to examine the effect of sales promotion and customer satisfaction on the intention to buy gadgets in Gorontalo. Gadgets have become an important part of everyday life, and sales promotions and customer satisfaction have a significant role in influencing consumer buying interest in gadgets. The research method used is a survey using a questionnaire distributed to respondents who are gadget users. The sample of this study consisted of 127 respondents who were randomly selected from various regions in Gorontalo. The data collected was then analyzed using the linear regression method. The results of the study show that sales promotion has a positive and significant influence on the intention to buy gadgets. The more intensive the sales promotion carried out by the gadget company, the higher the consumer's buying interest in the gadget. In addition, customer satisfaction also has a positive and significant influence on the intention to buy gadgets. When customers are satisfied with the gadget products and services they use, they tend to have a higher purchase intention to acquire the gadget.